Praying for known outcomes - Mawson, T (Cambridge University Press, 2007)
In this paper, I consider what difference knowledge of outcomes - both past and future - might make to the rationality of praying for them on a traditional theistic model. More specifically, I address four questions: Could it be rational to pray for outcomes one knows will obtain? Could it be rational to pray for outcomes one knows will not obtain? Could it be rational to pray for outcomes one knows have obtained? I argue that on certain common theistic assumptions, the answer to all of these questions is yes.